2019
DOI: 10.1016/j.isci.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation Regulates Primary Ciliary Length by Promoting Microtubule Disassembly

Abstract: Summary The sensory organelle cilium is involved in sensing and transducing important signaling cascades in almost all cells of our body. These ciliary-mediated pathways affect cellular homeostasis and metabolisms profoundly. However, it is almost completely unknown whether the cellular metabolic state affects the assembly of cilia. This study is to investigate how O-linked β-N-acetylglucosamine (O-GlcNAc), a sensor of cellular nutrients, regulates the cilia length. Pharmacologic or genetic inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…First, primary ciliary length negatively correlates with the cellular OGN levels both in hTERT-RPE1 and IMCD3 cells. Molecular mechanistic studies showed that OGN of α-tubulin and histone deacetylase 6 (HDAC6) are involved in ciliary shortening through promotion of axonemal microtubule disassembly [51]. Consistent with the work of Yu et al, primary cilia were fewer and shorter in the diabetic mouse eyes, trachea, and skin cells compared to those of wild type, and increased OGN of RPE1 cells in culture impaired ciliogenesis [52].…”
Section: The Nutrient Sensor O-glcnac Contributes To Primary Ciliary supporting
confidence: 55%
“…First, primary ciliary length negatively correlates with the cellular OGN levels both in hTERT-RPE1 and IMCD3 cells. Molecular mechanistic studies showed that OGN of α-tubulin and histone deacetylase 6 (HDAC6) are involved in ciliary shortening through promotion of axonemal microtubule disassembly [51]. Consistent with the work of Yu et al, primary cilia were fewer and shorter in the diabetic mouse eyes, trachea, and skin cells compared to those of wild type, and increased OGN of RPE1 cells in culture impaired ciliogenesis [52].…”
Section: The Nutrient Sensor O-glcnac Contributes To Primary Ciliary supporting
confidence: 55%
“…Although we need to take the alloxan result with a bit of caution (Alloxan is not a specific OGT inhibitor), Tian et al. also discovered a negative effect on cilia by O-GlcNAc ( 23 ), congruent with the results from Yu et al. ( 22 ).…”
Section: O-glcnac Negatively Regulates Cilia In Quiescent Cellssupporting
confidence: 54%
“…Two papers came out in 2018 and 2019, describing that O-GlcNAc exerts a negative effect on ciliogenesis and cilia lengths ( 22 , 23 ). Yu et al ( 22 ) first utilized DB mice that harbor diabetic mutations in the leptin receptor, and noticed that DB mice have fewer and shorter cilia than wild type.…”
Section: O-glcnac Negatively Regulates Cilia In Quiescent Cellsmentioning
confidence: 99%
“…A decrease in O-GlcNAcylation levels elevates autophagic flux by promoting the fusion of autophagosomes and lysosomes [ 6 , 25 ]. In the present study, we utilized small molecule inhibitors of OGT, alloxan [ 27 , 28 ], BZX2 [ 29 ], and OSMI-1 [ 30 ], and determined whether and how a decrease in O-GlcNAcylation contributes to autophagy in neurons. Collectively, our findings suggest that the inhibition of O-GlcNAcylation modification stimulates LC3-II expression and suppresses the autophagic substrate p62/SQSTM1 through the mTOR-dependent pathway, thereby revealing an important association between autophagy and O-GlcNAcylation in cortical neurons.…”
Section: Introductionmentioning
confidence: 99%